Letter (copy) : Assistance for Spain - Citrine, Walter, 1887-1983
030-0057-001 Secretary's WMC/HVT/CB. 17th September, 1938 Sir Daniel Stevenson, Cleveden, Glasgow, Dear Sir Daniel, Assistance for Spain. I received your letter of the 4th instant, and must apologise for the delay in answering, which -as you will appreciate - has been due to the pressure of matters connected with our recent Congress. The position at the moment is that we have already sent away all our available money. As you will probably be aware from reports in the papers, in accordance with a decision taken at Congress, a further appeal is being made. But for the time being it is neccesary to defer consideration of the request made in your letter. Yours sincerely, General Secretary. 292/946/30/57